Envelhecimento ambiental acelerado em PRF a base de tecidos híbridos kevlar/vidro: propriedades e instabilidade estrutural - Felipe, Renata Carla Tavares Santos (2012)
There are a number of damaging mechanisms that various materials can suffer in service. However, when working with polymer composite materials, this is something that requires analysis, especially when exposed to adverse environmental conditions. Thus, the objective of the present thesis is the study of the direct influence of environmental aging and the form of hybridization of the reinforcement woven on the structural stability, surfacedegradation and fracture process of polymer composites laminates. For this, the development of two polymer composite laminates was necessary, where one of them was reinforced with a bi-directional woven with hybrid strandsofkevlar-49/glass-Efibers, and the other also with a bi-directionalwoven, however with weft and warpformed of alternating strandsof Kevlar-49 fibers and glass-E fiber The reinforcementwoven are industrially manufactured. Both laminates use a polyester resin as a matrixand are made up of four layers each. All laminates were industrially prepared by the hand lay-up method of manufacturing. To do this, test specimens were manufactured of the respective laminates and submitted to environmental aging accelerated through the aging chamber. They were exposed to alternating cycles of UV radiation and moisture (heated steam) for a standard defined period. At the end of the exposure period the specimens were subjected to mechanical tests of uniaxial tensile and bending in three points and to the characterizationsof the fracture and surface deterioration. In addition, they were submitted to a structural degradation assessment by the measurement of mass variation technique (MMVT) and the measurement of thickness variation technique (MTVT), this last technique being developed in this thesis. At the end of the analysis it was observed that the form of hybridization of the reinforcement woven and the aging process directly influence with losses or gain in mechanical properties, with losses in the structural degradation and in the formation and propagation of damage mechanism of the developedcomposite laminates